Implementasi Terapi Bermain dengan Media Plastisin untuk Menurunkan Kecemasan pada Anak Usia Prasekolah di Ruang Anak RSUD Banjar - Rizki Solehudin; Novi Enis Rosuliana; Dini Mariani (Awatara Publisher, 2025)
Anxiety is a common problem experienced by children during hospitalization, which can affect their mental and physical health. To reduce their anxiety, play therapy using plasticine was conducted. Plasticine games do not require a lot of energy to play. This game can also be done on the child's bed so that it does not interfere with the child's health recovery process. In addition, plasticine games are suitable for preschool children because playing plasticine can increase children's imagination to make interesting things and improve children's fine imagination skills, so that children continue to develop even when hospitalized. This study aims to explore the effectiveness of play therapy in reducing children's anxiety levels. The method used was a case study involving two preschool children who experienced moderate anxiety. Play therapy was conducted over three days, with sessions lasting 20 minutes each. The results showed that play therapy with plasticine was successful in reducing preschool children's anxiety levels, as seen from the comparison of anxiety scores before and after the intervention. In addition, this therapy also provides opportunities for children to express their feelings and improve fine motor skills. Hopefully, the results of this study can be a reference for health workers in providing nursing care.